Enhancing store brand equity through relationship quality in the retailing industry: evidence from Vietnam - Minh Duy Vo; Si Van Nguyen (Cogent Business & Management, 2022)
Understanding the factors that contribute to store brand equity in the Vietnamese retailing industry is important. This study expands the "stimuli" components in the stimuli-organism-response (S-O-R) framework by considering the role of store information transparency and examining its contribution to store brand equity as an indirect "response" through relationship quality (trust, commitment, and satisfaction) and as the "organism" in the Vietnamese retailing setting. Quantitative research was conducted with a sample of 465 retail customers collected by the Ho Chi Minh City Statistical Office, Vietnam. Structural equation modeling was used to test the research hypotheses, and the results confirmed access convenience, store information transparency, and preferential treatment as the stimuli while relationship quality was the organism and store brand equity was the response. In a developing country such as Vietnam, store information transparency is important. Specifically, the dedication-constraint mechanisms based on social exchange theory together with the cultural norms of Vietnam's Confucian culture create a locked-in effect for the customer in the relationship with a retailer and resulted in high store brand equity. These findings offer insight into brand management literature and provide theoretical and managerial implications to increase the value of store brand equity in the Vietnamese retail industry.
Keywords: 650; access convenience; preferential treatment; relationship quality; S-O-R framework; store brand equity; store information transparency